Implementasi Peraturan Bupati Buton Selatan Nomor 23 Tahun 2017 tentang Pemilihan Kepala Desa dalam Penyelesaian Sengketa Pemilihan Kepala Desa Serentak di Kabupaten Buton Selatan - Mili, Sumarlin La; Muhaimin, La Ode; Faharudin, Faharudin (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Settlement of disputes over the election of village heads is the attributive authority of district/city regional heads based on Article 37 Paragraph (6) of Law Number 6 of 2014 concerning Villages, which states "in the event of a dispute over the results of the village head election, the regent/mayor shall resolve the dispute within the time period specified in referred to in paragraph (5)", in conjunction with Article 53 paragraph (1) South Buton Regent Regulation Number 23 of 2017 concerning Election of Village Heads which reads "In the event of a dispute over the results of the Village Head election, the Regent is obliged to resolve the dispute within a period of time. 30 (thirty) days”. However, the resolution of the dispute by the Regent still left a dispute, and resulted in a lawsuit at the State Administrative Court, this was because the nature of the Regent's decision could still be challenged (Beschikking). This research aims to determine the implementation of the South Buton Regent's Regulation Number 23 of 2017 concerning the Election of Village Heads in Resolving disputes over Simultaneous Village Election results in South Buton Regency. This research method is a normative juridical method, by conducting a review of library data or library research (Library Research). The model used is collecting legal materials and conducting analysis. The results of this research are that the Regulations for Settlement of Village Head Election Disputes in South Buton Regent Regulation Number 23 of 2017 concerning Village Head Elections are not regulated implicitly so that changes or separate arrangements need to be made as well as transferring authority in resolving Village Head Election Disputes in accordance with the division of power of an institution.